Expression of co-stimulatory molecules, chemokine receptors and proinflammatory cytokines in dendritic cells from normal and chronically inflamed rat testis - Rival, Claudia (2007)
The presentation of self antigens by dendritic cells (DC) plays an important role in the initiation and maintenance of autoimmunity. In a model of experimental autoimmune orchitis (EAO), we have previously characterized dominant testicular autoantigens and shown an increase in DC numbers during the course of disease. In this study, we have developed a protocol for the isolation of a highly pure population of DC (∼97%) from the testis of EAO and control rats to analyse the expression of major histocompatibility complex (MHC) class II and co-stimulatory molecules (CD80, CD86), chemokine receptors (CCR2, CCR7) and cytokines (IL-10, IL-12p70, TNF-α). By flow cytometry, we observed similar percentage and intensity levels of MHC class II, CD80 and CD86 expression in testicular DC in all groups. Moreover, by real-time RT-PCR we have detected significantly higher CCR7 mRNA level in isolated testicular DC from rats with EAO compared to controls, whereas the expression of CCR2 was decreased in orchitis. Transcripts of IL-12p40 were observed in DC from all groups, whereas the expression of IL-10 and the rate limiting IL-12 subunit p35 were detectable exclusively in testicular DC from the inflamed testes. In co-culture experiments, testicular DC isolated from EAO animals significantly enhanced naïve T-cell proliferation compared with control DC. Taken together these results suggest that testicular DC in control testis is not mature and functionally tolerogenic, whereas in EAO testis, IL-12 expression and stimulation of T-cell proliferation points to a mature immunogenic state prior imminent migration to the lymph nodes to amplify immune responses against testicular antigens.